Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan PT Musi Hutan Persada - Yudi Tusri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
This study aims to determine the effect of leadership style and motivation on employee performance on PT Musi Hutan Persada (KPO Niru Case Study). The analysis tools used are test of multiple linear regression, T test, F test, test the coefficient of multiple determination. Based on the results it can be concluded that the leadership style variable (X1) and the motivation variable (X2) affect positive and significant impact on the employee’s performance. Hypothesis test indicates that leadership and motivation style have a positive and significant influence on employee performance. This means tha Ha is acceptable. It can be concluded that, the leadership and motivation style has a positive and significant influence on the employee’s performance at PT Musi Hutan Persada KPO Niru. Keywords : Leadership Style, Motivation and Employee Performance.